Propuesta para la modificación del impuesto al valor agregado en época invernal - Piza Abad, Daniel Bartolo (2018)
From Law No. 56 of Régimen Tributario Interno published in Registro Oficial No. 341 of December 22, 1989, which creates the Value Added Tax (VAT), replacing the Tax on Commercial Transactions and Provision of Services ( ITMPS). In Ecuador, the rate of Value Added Tax is determined in Article 65 of the Ley Orgánica de Régimen Tributario Interno, this tax was born in 1989 with a rate of 10%, which increased in 1997 to 12%. fixed, until 2016, which increased to 14%, due to the earthquake suffered by Ecuador in April 2016, this increase lasted only one year, in this period although the revenue increased was not at the expected levels in addition to bringing the counterproductive effect of increasing the final prices of goods and services, an effect that depressed consumption….